1986
DOI: 10.2466/pms.1986.62.2.659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, Etiology, and Hearing Loss on Balance Performance by Deaf Children

Abstract: The purpose of this study was to examine the influence of age, sex, etiology, and degree of hearing loss on the static and dynamic balance performance of hearing impaired children and youth (N = 132), ages 3 to 14 yr. The subjects were individually assessed on Items 2 and 7 of Subtest 2 of the Short Form of the Bruininks-Oseretsky Test of Motor Proficiency. As expected, performance on both tasks improved with chronological age. In comparing the performance of subjects by etiology, only one significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Mecanismo semelhante de plasticidade é observado também para células sensoriais do sistema vestibular que foram lesadas (Hara, Takeno, Shimogori, & Yamashita, 2005 (Brunt & Broadhead, 1982;Brunt et al, 1987;Savelsbergh & Netelenbos, 1992). As pesquisas também mostram que o desempenho de surdos em testes de equilíbrio melhora com a idade (Butterfield & Ersing, 1986) e com oportunidades de experiências motoras (Campos, 2003;Rine et al, 2004). (Dummer, Haubenstricker, & Stewart, 1996).…”
Section: Composição Número De Pulsosunclassified
“…Mecanismo semelhante de plasticidade é observado também para células sensoriais do sistema vestibular que foram lesadas (Hara, Takeno, Shimogori, & Yamashita, 2005 (Brunt & Broadhead, 1982;Brunt et al, 1987;Savelsbergh & Netelenbos, 1992). As pesquisas também mostram que o desempenho de surdos em testes de equilíbrio melhora com a idade (Butterfield & Ersing, 1986) e com oportunidades de experiências motoras (Campos, 2003;Rine et al, 2004). (Dummer, Haubenstricker, & Stewart, 1996).…”
Section: Composição Número De Pulsosunclassified
“…Potter and Newman Silverman (1984) examined balance skill in children with hearing impairment and no significant sex differences were found in the vestibular or balance status of the deaf children. Butterfield and Ersing (1986), also, found no relationship between gender and performance on dynamic and static balance tasks in children ages 3-14 years, with hearing impairment.…”
Section: Relationship Between Gender Type Of Sensor Impairment and Momentioning
confidence: 99%
“…The purpose of Butterfield and Ersing (1986) study was to examine the influence of age, sex, etiology and degree of hearing loss on the static and dynamic balance performance of www.intechopen.com hearing impaired children and youth, ages 3 to 14 years. The subjects were individually assessed on Items 2 and 7 of Subtest 2 of the Short Form of the Bruininks-Oseretsky Test of Motor Proficiency.…”
Section: Relationship Between Age Type Of Sensor Impairment and Motomentioning
confidence: 99%
“…In studies by Butterfield and Ersing and by Siegel et al, in which hearing-impaired children (hearing loss >60 dB) aged between 3 and 14 were tested using a version of the "Bruininks-Oseretsky Test of Motor Proficiency" which was restricted to balance exercises, it was found that postural stability consistently increased with age [5,31].…”
Section: Agementioning
confidence: 99%
“…None of the following investigators found that gender influenced the performance of the children studied: Lindsey and O'Neal, Butterfield and Ersing, Siegel et al and Rine et al, who investigated deaf and hearing-impaired children using motor tests [3][4][5]31]; Potter and Silverman [9] and Gayle and Pohlmann [2], who also incorporated vestibuloocular function (postrotatory); and Foudriat et al [16], who performed EquiTest ® trials on normal 3-6 year-old children.…”
Section: Gendermentioning
confidence: 99%